Effect of Reinforcement of Hybrid Layer FRP (GFRP and CFRP) on Bending Behavior of Reinforced Concrete Beams - Jasman; Rudy Djamaluddin; Rita Irmawaty; A. Arwin Amiruddin (Nusantara Science and Technology Proceedings, 2022)
FRP (Fiber Reinforced Polymer), such as glass fiber or GFRP (glass fiber reinforced polymer) and carbon fiber or CFRP (carbon fiber reinforced polymer), are environmentally friendly materials that can be added to structural materials. This material has a high level of flexibility and resistance, corrosion resistance, and elasticity, with low installation costs, so it has the potential as a building material, especially in earthquake-resistant areas. This study aims to determine the flexural capacity of standard reinforced concrete beams with hybrid FRP layer reinforcement (GRFP-s and CFRP-s) using various glass fiber and carbon fiber concentrations. The research was designed by designing loads and beams for the flexural capacity of reinforced concrete beams using FRP Hybrid layers (GFRP-s and CFRP-s). Six specimens of reinforced concrete beams were made with 2 specimens, namely BN (standard beams without using U-wrap and FRP) and BGC (beams using 2 layers of FRP reinforcement, namely GFRP-s and CFRP-s using U- wrap GFRP- s). Load cell readings for beam testing are carried out every 1 kN loading. Three LVDT (Linear Variable Displacement Transducers) are installed at the bottom of the beam to record the deflection in the beam. Installation of Strain Gauge (SG) to measure the beam's pressure and (deformation or strain). The test was carried out on a frame made of steel profiles designed with simple bearings (roll-joints) to test the flexural strength of the beam with a beam length of 3300 mm and a rectangular cross- section with dimensions of 150 x 200 mm. The results showed that the addition of FRP with 100% GRFP and 75% CFRP had optimum stress with a significant strain value, so it was perfect for flexural reinforcement of reinforced concrete.